Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the system of equations step by step to determine which statement is true.
We are given the system of equations:
1. [tex]\( 2y - 4x = 6 \)[/tex]
2. [tex]\( y = 2x + 3 \)[/tex]
#### Step 1: Substitute Equation 2 into Equation 1
Since [tex]\( y = 2x + 3 \)[/tex], we can substitute [tex]\( y \)[/tex] into the first equation:
[tex]\[ 2(2x + 3) - 4x = 6 \][/tex]
#### Step 2: Simplify the Equation
Expand and simplify the left-hand side:
[tex]\[ 4x + 6 - 4x = 6 \][/tex]
This simplifies to:
[tex]\[ 6 = 6 \][/tex]
#### Step 3: Analyze the Result
The equation [tex]\( 6 = 6 \)[/tex] is always true regardless of the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex]. This indicates that the original equations are not independent; they represent the same line.
#### Finding the Relationship between the Equations
Let's derive [tex]\( y \)[/tex] from both equations to see the relationship more clearly.
From Equation 1:
[tex]\[ 2y - 4x = 6 \][/tex]
[tex]\[ y = 2x + 3 \][/tex]
From Equation 2:
[tex]\[ y = 2x + 3 \][/tex]
Both equations simplify to [tex]\( y = 2x + 3 \)[/tex], which means they are the same line.
#### Conclusion
Since both equations represent the same line, there are infinitely many solutions where any [tex]\((x, y)\)[/tex] that satisfies [tex]\( y = 2x + 3 \)[/tex] is a solution.
#### Answer
Given the analysis above:
D. The system has infinitely many solutions.
We are given the system of equations:
1. [tex]\( 2y - 4x = 6 \)[/tex]
2. [tex]\( y = 2x + 3 \)[/tex]
#### Step 1: Substitute Equation 2 into Equation 1
Since [tex]\( y = 2x + 3 \)[/tex], we can substitute [tex]\( y \)[/tex] into the first equation:
[tex]\[ 2(2x + 3) - 4x = 6 \][/tex]
#### Step 2: Simplify the Equation
Expand and simplify the left-hand side:
[tex]\[ 4x + 6 - 4x = 6 \][/tex]
This simplifies to:
[tex]\[ 6 = 6 \][/tex]
#### Step 3: Analyze the Result
The equation [tex]\( 6 = 6 \)[/tex] is always true regardless of the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex]. This indicates that the original equations are not independent; they represent the same line.
#### Finding the Relationship between the Equations
Let's derive [tex]\( y \)[/tex] from both equations to see the relationship more clearly.
From Equation 1:
[tex]\[ 2y - 4x = 6 \][/tex]
[tex]\[ y = 2x + 3 \][/tex]
From Equation 2:
[tex]\[ y = 2x + 3 \][/tex]
Both equations simplify to [tex]\( y = 2x + 3 \)[/tex], which means they are the same line.
#### Conclusion
Since both equations represent the same line, there are infinitely many solutions where any [tex]\((x, y)\)[/tex] that satisfies [tex]\( y = 2x + 3 \)[/tex] is a solution.
#### Answer
Given the analysis above:
D. The system has infinitely many solutions.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.